2007
DOI: 10.1007/s11224-006-9142-x
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and characterization of mononuclear copper(II) and cadmium(II) complexes with di-(2-picolyl)sulfur

Abstract: The reaction of Cu(ClO 4 ) 2 · 6H 2 O and Cd(ClO 4 ) 2 with di-(2-picolyl)sulfur (dps) leads to the formation of mononuclear complexes [Cu(dps)(H 2 O)(ClO 4 )](ClO 4 ) (1) and [Cd(dps) 2 ](ClO 4 ) 2 (2). The crystal structure of 1 exhibits a distorted square pyramidal geometry, coordinated by one sulfur and two nitrogen atoms from the dps ligand, one water molecule and one perchlorate oxygen atom. For 2, the environment around cadmium atom is in a distorted octahedron with four nitrogen and two sulfur atoms fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2008
2008
2011
2011

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 24 publications
1
1
0
Order By: Relevance
“…Compared with CVs of the complex, the ligand exhibits an analog broad current respond around 0.7-1.2 V. Therefore, we propose that the response at the range of 0.2-0.9 V is due to the electrochemical reaction of the ligand on the electrode. According to the above analysis, it can be concluded that the oxidation peak (Ep = -0.7 V) is probably assigned to the oxidation peak of Cd ?2 /Cd 0 , and because of the absence of the corresponding reduction peak, the oxidation of the complex can be considered as an irreversible process, similar with the reported [45,46].…”
Section: Electrochemical Properties Of the Complex [Cd(pmp) 2 ] Nsupporting
confidence: 79%
“…Compared with CVs of the complex, the ligand exhibits an analog broad current respond around 0.7-1.2 V. Therefore, we propose that the response at the range of 0.2-0.9 V is due to the electrochemical reaction of the ligand on the electrode. According to the above analysis, it can be concluded that the oxidation peak (Ep = -0.7 V) is probably assigned to the oxidation peak of Cd ?2 /Cd 0 , and because of the absence of the corresponding reduction peak, the oxidation of the complex can be considered as an irreversible process, similar with the reported [45,46].…”
Section: Electrochemical Properties Of the Complex [Cd(pmp) 2 ] Nsupporting
confidence: 79%
“…Next, mononuclear Cu(II) and Cd(II) complexes with di-(2-picolyl)sulfide were synthesized and characterized by Choi et al [137]. The divalent and trivalent transition metal complexes with NNS and NNN donor ligands have been of great interest because of their importance as an analytical chelate reagent, for biological and bacteriostatic activity [138][139][140][141][142][143].…”
Section: Issuementioning
confidence: 99%